1-[3-(Anthracen-9-yl)-5-(pyridin-2-yl)-4,5-dihydro-1H-pyrazol-1-yl]ethanone - Zhang, Shi-Lu (International Union of Crystallography, 2012)
In the title compound, C(24)H(19)N(3)O, the pyrazoline ring adopts an envelope conformation with the C atom linking to the pyridine ring as the flap. The mean plane of the pyrazoline ring makes dihedral angles of 85.54 (4) and 81.66 (3)° with the pyridine ring and the anthracene ring system, respectively. In the crystal, molecules are linked by C—H⋯O hydrogen bonds. In addition, weak π–π interactions [centroid–centroid distances = 3.695 (3)–3.850 (7) Å] are observed.